Therapeutic approach of a pancreatic Ewing Sarcoma/PNET: case report and literature review - Pinheiro, Rodrigo Nascimento; Cesário, Fabiane Kellem Oliveira dos Santos; Mondragon, José Pablo Mata; Silva, Fábio Daniel Barbosa da; Fontoura, Renata Pereira; Sousa, José Donato de, Netto; Botelho, Carlos Henrique de Aguiar (Brazilian Journal of Oncology, 2020)
Peripheral primitive neuroectodermal tumors (pPNETs) are part of the Ewing sarcoma family. A few more than 30 cases of pPNETs originating on the pancreas have been reported in the consulted literature. We report a locally advanced pancreatic pPNET, with the longest follow-up and survival in the consulted literature, considering quality of life outcomes. 22-year-old male patient, with a pancreatic pPNET comprising pancreatic body and tail with gastric invasion. He underwent multi organic resection and adjuvant chemotherapy and radiotherapy. After 8 years of follow-up, he was free of disease and with a good quality of life self-evaluation. The aggressive surgical approach associated with multimodal regimens provided improvement in disease-free survival and a positive impact on quality of life.
Keywords: Neuroectodermal tumors; Primitive; Peripheral; Sarcoma; Ewing; Pancreatic neoplasms; Combined modality therapy; Quality of life